Analysis of the Chinese martial periodicals edited during the Republican Era - Acevedo, William; Cheung, Mei (Revista de Artes Marciales Asiáticas, 2012)
The present article studies the periodicals and magazines published during the Chinese Republican period (1912-1949). The main sources for this work are the index and thirty volumes of the Republican Era Collection of National Arts Periodicals (Mingguo Guoshu Qi Kan Wenxian Jicheng), edited by Shi Yong Xing in 2008. Besides basic data about the 45 publications included in the collection such as title, editor, publication information and period of existence; this article emphasises the historical context in which these publications appeared as well as their efforts to help China becoming a nation recognized at the world stage. As an example of the wealth of information contained in these periodicals regarding Chinese martial arts, we have analyzed the terminology that was used to define them, the publications’ contribution to exalt nationalism up to their influence in strengthening of China’s citizens and military.